2012
DOI: 10.1111/j.1442-2050.2011.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socioeconomic environment on survival in patients diagnosed with esophageal cancer: a population-based study

Abstract: The influence of social environment on survival in patients with cancer has been demonstrated in many studies, subjects living in the most deprived areas having a poorer prognosis. Geographic remoteness and limited access to specialized care centers are often associated with socioeconomic deprivation. The aim was to assess the influence of social environment and geographic remoteness on the relative survival of patients diagnosed with esophageal cancer between 1997 and 2004 in the department of Calvados in Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 34 publications
0
31
0
2
Order By: Relevance
“…These studies have reported that individual and neighborhood socioeconomic status are independently associated with cancer survival and also interact . Thus, inequalities found in studies on area‐based deprivation might also be caused by community characteristics like distance and access to specialized care centers or geographical remoteness . Our measure of deprivation does not cover the domain health care provision in the district.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported that individual and neighborhood socioeconomic status are independently associated with cancer survival and also interact . Thus, inequalities found in studies on area‐based deprivation might also be caused by community characteristics like distance and access to specialized care centers or geographical remoteness . Our measure of deprivation does not cover the domain health care provision in the district.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond racial disparities, socioeconomic status (SES), as measured by income level or degree of education, also recently was associated with multiple poor health outcomes, including diabetes, cardiovascular disease, and cancer . Population cohort studies in lung and esophageal cancers have suggested that one's social environment, as defined by area‐based socioeconomic measures, may be associated with worse survival outcomes, possibly due to poor screening or receipt of therapy . Such class disparities ultimately may mitigate improvements in outcomes, and warrant further evaluation to identify root causes of poor health and inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…12 Population cohort studies in lung and esophageal cancers have suggested that one's social environment, as defined by area-based socioeconomic measures, may be associated with worse survival outcomes, possibly due to poor screening or receipt of therapy. [13][14][15] Such class disparities ultimately may mitigate improvements in outcomes, and warrant further evaluation to identify root causes of poor health and inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…There are two type of esophageal cancer (EC) based on histology – squamous cell carcinoma and adenocarcinoma; both are highly lethal, with a 5-year survival rate <10% (24). An esophageal “cancer belt,” primarily squamous cell cancers (ESCC), extends from northeast China to the Middle East (5, 6).…”
Section: Introductionmentioning
confidence: 99%